2020
DOI: 10.1155/2020/1483827
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Predictors and Associated Factors in Patients in the Intensive Care Unit: A Cross-Sectional Study

Abstract: Background. Mortality in the intensive care unit (ICU) has been associated to an array of risk factors. Identification of risk factors potentially contribute to predict and reduce mortality rates in the ICU. The objectives of the study were to determine the prevalence and the factors associated with the mortality and to analyze the survival. Method. A cross-sectional study conducted in two clinical and surgical ICU in the state of Sergipe, northeastern Brazil. We enrolled 316 patients with at least 48 h of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
(46 reference statements)
0
18
1
4
Order By: Relevance
“… 1 Infections, presence of underlying disease, length of hospitalization, sedation, mechanic ventilation, use of vasopressors drugs, advanced age of the patient, and interventional procedures increase mortality. 2 The mean death rate of ICU noticed in the United States is between 8 and 19%, and annual deaths are reported as approximately 500,000 people. 1 In studies reported from our country, the ICU mortality rate was reported to be between 20.5 and 40.2%.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Infections, presence of underlying disease, length of hospitalization, sedation, mechanic ventilation, use of vasopressors drugs, advanced age of the patient, and interventional procedures increase mortality. 2 The mean death rate of ICU noticed in the United States is between 8 and 19%, and annual deaths are reported as approximately 500,000 people. 1 In studies reported from our country, the ICU mortality rate was reported to be between 20.5 and 40.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Outrossim, a idade é um fator que precede o desenvolvimento das doenças crônicas como Alzheimer, cânceres, doenças neurodegenerativas e cardiovasculares, além da fragilidade, imobilidade e delirium que são associados à morbimortalidade, hospitalização e custos no sistema de saúde mundial (Oh et al, 2017;Parant, 1990). Delirium é um estado agudo confusional, frequente em idosos, caracterizado por início agudo, nível alterado de consciência, curso flutuante e distúrbios na orientação, memória, atenção, pensamento desorganizado e comportamento (Oh et al, 2017;Tchkonia et al, 2018), pode ser associado à doenças graves (Pinheiro et al, 2020), ou não, e a prevalência no departamento de emergência varia de 7 a 10%, em idosos (Átilla et al, 2014), porém apenas 16% a 35% dos casos são diagnosticados (Elie et al, 2000;Hustey & Meldon, 2002).…”
Section: Introductionunclassified
“…Este estado confusional é, também, um evento adverso, que repercute na qualidade de cuidado (Pinheiro et al, 2020), associado à piores desfechos (Schubert et al, 2018) Pacientes idosos com delirium possuem 1,5 maior risco de óbito (Smith & Meyfroidt, 2017) e duplicam o tempo de permanência no hospital, o que acarreta no dobro de horas de profissionais de saúde e dobram os custos totais da internação por paciente (Pinheiro et al, 2020).…”
Section: Introductionunclassified
“…The intensive care unit (ICU) provides a continuous monitoring system for critically ill patients with potential for rehabilitation or life-threatening diseases and is committed to providing targeted monitoring and best care. [ 1 ] Due to the high fatality rate and expensive medical resources, the ICU has attracted extensive attention in the medical community. [ 2 ] To facilitate continuous monitoring of all patients and ensure that any deterioration of their condition is detected and corrected before it becomes a fatal disease, the ICU staff to patients ratio is often very high, which has been proven to improve results.…”
Section: Introductionmentioning
confidence: 99%